Middle Eastern plant extracts: an alternative to modern medicine problems - Varijakzhan, Disha; Chong, Chou Min; Abushelaibi, Aisha; Lai, Kok Song; Lim, Erin Swee Hua (MDPI, 2020)
Middle Eastern countries are primarily known for their dry sand deserts; however, they have a wider physiographic range which includes upland plateau and mountain ranges. The Middle East is home to various types of plants, such as Phoenix dactylifera (date palm tree), Scrophularia striata (herbaceous plants), and Opuntia ficus-indica (cactus). These plants have been found to have various types of bioactivities, such as antimicrobial activities against both bacteria and fungi, in addition to exhibiting anti-inflammatory effects and anti-cancer characteristics which can be utilized in the clinical setting for treatment. Due to limited reviews focusing on plant extracts from the Middle East, we aim to provide a discourse on plants from this region which have various bioactivities and to provide information on the compounds that can be identified from these plants. This is to enhance our understanding to improve modern medicine problems such as antimicrobial resistance and to find an alternative cure for cancer. It is hoped that the collation of information from this review will enable an assessment of the direct role of Middle Eastern plants in providing therapeutic options to address the predicaments in the medical field.